Orthology‐based analysis helps map evolutionary diversification and predict substrate class use of BAHD acyltransferases. (27th July 2022) - Kruse, Lars H.; Weigle, Austin T.; Irfan, Mohammad; Martínez‐Gómez, Jesús; Chobirko, Jason D.; Schaffer, Jason E.; Bennett, Alexandra A.; Specht, Chelsea D.; Jez, Joseph M.; Shukla, Diwakar; Moghe, Gaurav D.
SUMMARY: Large enzyme families catalyze metabolic diversification by virtue of their ability to use diverse chemical scaffolds. How enzyme families attain such functional diversity is not clear. Furthermore, duplication and promiscuity in such enzyme families limits their functional prediction, which has produced a burgeoning set of incompletely annotated genes in plant genomes. Here, we address these challenges using BAHD acyltransferases as a model. This fast‐evolving family expanded drastically in land plants, increasing from one to five copies in algae to approximately 100 copies in diploid angiosperm genomes. Compilation of >160 published activities helped visualize the chemical space occupied by this family and define eight different classes based on structural similarities between acceptor substrates. Using orthologous groups (OGs) across 52 sequenced plant genomes, we developed a method to predict BAHD acceptor substrate class utilization as well as origins of individual BAHD OGs in plant evolution. This method was validated using six novel and 28 previously characterized enzymes and helped improve putative substrate class predictions for BAHDs in the tomato genome. Our results also revealed that while cuticular wax and lignin biosynthetic activities were more ancient, anthocyanin acylation activity was fixed in BAHDs later near the origin of angiosperms. The OG‐based analysis enabled identification of signature motifs in anthocyanin‐acylating BAHDs, whose importance was validated via molecular dynamic simulations, site‐directed mutagenesis and kinetic assays. Our results not only describe how BAHDs contributed to evolution of multiple chemical phenotypes in the plant world but also propose a biocuration‐enabled approach for improved functional annotation of plant enzyme families. Significance Statement: Large enzyme families contribute significantly to the metabolic diversity observed in plants, but our knowledge about how these families attain such functional diversity and whether we can predict their functions is limited. To address these challenges, we used an orthology‐based approach coupled with extensive curation of functional data from literature, using the BAHD acyltransferase family as a model. This approach helped predict BAHD substrate class use and provided insights into the family's functional diversification during the evolution of the plant kingdom.